The places that scare you : A guide to fearlessness - Chodron, Pema. (London : Element, 2003)
Dealing with difficult time and problems that come your way.
Includes bibliographical references.
Keywords: Religious life -- Buddhism; Buddhism -- Doctrines; Religious life